Cranial osteogenesis and suture morphology in Xenopus laevis: a unique model system for studying craniofacial development. - Bethany J Slater; Karen J Liu; Matthew D Kwan; Natalina Quarto; Michael T Longaker (PLoS ONE, 2009)
BACKGROUND:The tremendous diversity in vertebrate skull formation illustrates the range of forms and functions generated by varying genetic programs. Understanding the molecular basis for this variety may provide us with insights into mechanisms underlying human craniofacial anomalies. In this study, we provide evidence that the anuran Xenopus laevis can be developed as a simplified model system for the study of cranial ossification and suture patterning. The head structures of Xenopus undergo dramatic remodelling during metamorphosis; as a result, tadpole morphology differs greatly from the adult bony skull. Because of the extended larval period in Xenopus, the molecular basis of these alterations has not been well studied. METHODOLOGY/PRINCIPAL FINDINGS:We examined late larval, metamorphosing, and post-metamorphosis froglet stages in intact and sectioned animals. Using micro-computed tomography (microCT) and tissue staining of the frontoparietal bone and surrounding cartilage, we observed that bone formation initiates from lateral ossification centers, proceeding from posterior-to-anterior. Histological analyses revealed midline abutting and posterior overlapping sutures. To determine the mechanisms underlying the large-scale cranial changes, we examined proliferation, apoptosis, and proteinase activity during remodelling of the skull roof. We found that tissue turnover during metamorphosis could be accounted for by abundant matrix metalloproteinase (MMP) activity, at least in part by MMP-1 and -13. CONCLUSION:A better understanding of the dramatic transformation from cartilaginous head structures to bony skull during Xenopus metamorphosis may provide insights into tissue remodelling and regeneration in other systems. Our studies provide some new molecular insights into this process.